PERTUMBUHAN EKONOMI DAN KESEMPATAN KERJA DI SULAWESI TENGGARA - Muhammad Syarif (Universitas Halu Oleo, 2017)
The purpose of this study is to reveal the link between economic growth, capital formation, and employment opportunities in the economic development of Southeast Sulawesi. This research uses descriptive narrative analysis method to explain the relationship between economic growth and employment opportunities in Southeast Sulawesi in the period 2002-2006 where secondary data was sourced from publications by the Central Sulawesi Provincial Statistics Agency (BPS). The results showed that the economic development (PDRB) of Southeast Sulawesi in the 2002-2006 period in absolute terms continued to increase or grow an average of 7.52 percent per year. The GRDP structure is dominated by the service sector, followed by the agricultural and industrial sectors. Labor absorption is still dominated by the agricultural sector, followed by the service and industrial sectors. GRDP according to usage of approximately 80 percent is used for consumption expenditures consisting of household consumption expenditure of almost 60 percent, non-profit consumption expenditure of about 0.3 percent, and government consumption expenditure of more than 21 percent. The number of workforce continues to increase, while the development of the number of opportunities and unemployment rates fluctuate from year to year.